Role of intraperitoneal instillation of bupivacaine after laparoscopic cholecystectomy for post-operative pain management: a randomized controlled trial - Datta, Pramatha Nath; Roy, Arijit (International Surgery Journal, 2020)
Background: Intra peritoneal (IP) local anaesthesia (LA) is a simple, cheap and safest method of providing post-operative (post-op) analgesia after laparoscopic cholecystectomy (LC). In this research, the role of intraperitoneal (IP) instillation of bupivacaine on post-op pain was studied. Post-op pain at 6, 12 and 24 hours was assessed using numeric rating scale. The degree of ambulation postoperatively at 6 and 24 hours and the requirement of analgesics was taken into account. The length of hospital stay was also a factor. Methods: A total of 76 patients during January 2018 to December 2018, undergoing LC, fitting the inclusion criteria were included randomly and divided in to two groups, bupivacaine group (B) and control group (A) based on a pre-generated random number sequence by the principal investigator. The surgical outcome was compared based on multiple parameters and the primary outcome measures were the post-op pain and analgesic requirement. Results: Degree of ambulation at 6 hours was significantly better in group B, compared to group A (p=0.008). The requirement of first dose of rescue analgesia was found to be within 6 hours (post-op) in 34 patients of group A (89.47%) as compared to 13 patients of group B (34.21%), was found to be statistically significant (p<0.001). There was statistically significant (p=0.002) difference with respect to length of hospital stay between the two groups. Conclusions: In our study we found that IP bupivacaine (0.5%) is an effective, economical, safe method of post-op pain management with better post-op recovery.